Палеоліт і мезоліт у печерах Заходу України - Мацкевий, Л.Г. (Археологический альманах, 2000)
Як відомо, саме у західному регіоні України знаходиться значне скупчення печерних порожнин . Багато з них досить пізнього походження, а ранні утвори часом зруйновані, або перекриті (поховані) значними відкладами і тому є малодоступними. Деякі печери мають високу постійну вологість, у них велика небезпека обвалів, поблизу відсутні водні джерела і несприятлива екологічна ситуація у цілому. Але окремі печерно-скельні ансамблі дають значну кількість об'єктів матеріальної і духовної культури. Доба палеоліту і мезоліту у регіоні співпадає з періодом кінця плейстоцену - початком голоцену, який тут поки ще недостатньо висвітлений в узагальнюючих природознавчих працях. It is well-known, that in this region a rich concentration of caves has beer; discovered. For the last decade in these natural formations, sites of Palaeolithic and Mesolithic age were discovered and thoroughly studied. For the Mousterian age it is a settlement at Pryima I grotto. Characteristic of the late Palaeolithic age are the Late Gravettian complex in Pryima I shelter and sites with Aurignacian and Postaurignacian features in Lviv VII shelter (three cultural strata), as well as in caves of Molochnyj Karnin, Tchortovets (Nazarenkove I) and Dumka (Odayiv XI). Sites of Mesolithic age have been identified in the following shelters: Lviv VII, VIII, Pidgorodci IV and Pryima I, at grottoes of Pryima VII and Blazhenny Karnin (Maniava I), in Nigyn I cavern, and in Balamutivka I - possibly a site of primitive art. Most are of Mesolithic age in Nezvysko-Oselivka. Obviously, there were almost exceptionally hunter camps, which were visited by people during cold seasons. Placement of almost all major sites in the areas of steepvalbyson canyons, as well as for classic solutrean site, clearly evidences the drive hunting technique. In hilly conditions, this did not exclude an ambush way of hunting. Stone and bone articles, works of primitive art, numerous faunal remains and other artefacts testify to significant abilities of ecological niche of the region and a high level in development of material and mental culture. In cavernous-rocky ensembles, the components of cultural strata are better preserved than in open-air sites. It gives additional opportunities for complex conciousness of the materials - application of various methods and more quantities of analyses,than for artifacts from open-air sites.